Objective Determination of the Withdrawal Dates of the Southwest Monsoon (Habagat) Season of the Philippines Using Cumulative Rainfall - Olaguera, Lyndon Mark P. (Archīum Ateneo, 2024)
This study investigates the climatological characteristics of the withdrawal period of the southwest monsoon (henceforth, Habagat) season using daily rainfall records from 11 weather stations of the Philippine Atmospheric, Geophysical, and Astronomical Services Administration located along the west coast of the Philippines from 1979– 2020. The withdrawal dates were objectively determined by iterative fitting of two-phase linear regression models on the cumulative time series of rainfall in each year and station. The cumulative time series were bootstrapped, and the withdrawal detection was applied in each bootstrap sample to estimate the lower (25th percentile) and upper (75th percentile) confidence limits. The average withdrawal date across the 11 stations was found to occur on 21 Oct, with confidence limits of –6 and 11 d. Using the same index, the average onset date was also obtained, and the average duration was estimated. The average duration of the Habagat season is about 148 d. No significant correlation was found between the onset and withdrawal dates, indicating that the duration of the Habagat season is mainly controlled by its withdrawal. The withdrawal period is characterized by a gradual decrease in rainfall and relative humidity along the western coastal stations, strengthening of the easterlies from the Pacific Ocean, as well as the southward migration of the monsoon trough and western North Pacific subtropical high. Further analysis showed that there is no clear relationship between ENSO and the withdrawal dates obtained in this study. However, there were notable years such as 2010 and 2020, both being La Niña years, when the withdrawal dates were delayed by at least 20 d. This study is the first attempt to characterize the withdrawal of the Habagat season, and the index used in this study may be useful for agricultural planning and management of hydrological resources in the Philippines.